Correlation and path analyses on morphometric traits and body mass of F5 generation breeding population in sea cucumber (Apostichopus japonicus) - HAN Sha; HU Wei; LI Chenglin; LI Wenwen; ZHAO Bin; QU Hongxia; WANG Qi; YAO Linlin (浙江大学学报. 农业与生命科学版, 2022)
In order to explore the relationships between morphometric traits and body mass (BM) of sea cucumber (Apostichopus japonicus), correlation analysis and path analysis were used to obtain the main morphometric traits affecting body mass. Three morphometric traits including body length (BL), body width (BW) and body mass of 366 individuals of F5 generation breeding population at one year old were measured, and one compound index that combined body length and body width to produce the square root of the length-width (SLW) index was calculated. The results showed that the correlation coefficients between morphometric traits and body mass were highly significant. The stepwise regression analysis showed that morphometric traits (SLW and body width) and body mass were significantly positive correlations (P＜0.001). Based on path coefficients, the multiple linear regression mode equation on the effects of body mass was established as BM=－16.14+6.70SLW+4.31BW. The morphometric traits that directly affected body mass were SLW＞BW, and SLW was the main morphometric trait that significantly affected body mass and its path coefficient was 0.62. Body width had an indirect effect on the body mass via SLW. The fitting relationships between morphometric traits and body mass were expressed as following BM=0.39SLW2.66 (R2=0.86, P＜0.001), showing negative allometry tendency. The results provide valuable information and theoretical guidance for A. japonicus breeding programs. Body width should be selected directly and body length simultaneously, when body mass is the breeding target.